Analisis Seni Pertunjukan Arja Muani Di Bali: Dari Dominasi Maskulinitas ke Fluid Gender Tahun 1997 - 2022 (Jurnal Nawala Politika, 2022)
This study aims to determine the performance of gender (fluid gender) in arja muani work as a performing art in Bali, by analyze at the forms of representation in the arja muani’s performing arts in Bali with Butler's theory of gender performativity (1990). The research results is: First, the Arja Muani performances were modified by several players following the times. Second, there are pros and cons of modifications in the performing arts of arja muani among the performers. Third, this contra attitude then shows the existence of very masculine thoughts and views, created by the arja muani performers with a fluid gender appearance on stage (representation). Fourth, the modifications made by some Arja Muani players are in fact considered to have deviated from the existing standards (cons). Fifth, actors who agree with the modifications in arja muani (pro) tend to present more fluid gender on and off stage (presentation).